Mediating Role of Work Environment in The Effect of Occupational Health, Safety Management System, And Teamwork over Patient Safety Climate According to Nurses’ Perception - Roveny Roveny; Rokiah Kusumapradja; CSP Wekadigunawan (Penerbit Kemala Indonesia, 2020)
Patient safety has been recognized as the biggest challenge in the global public health system. A good patient safety climate initiates planning for safe care. Also, the patient safety climate issue has become a top priority in the X Hospital. This study aims to reveal empirical evidence of the effect of occupational health and safety management systems, teamwork on patient safety climate with the mediation effect over work environment based on empirical research. In this research, we use cross-sectional method to processed path analysis with a 49 of total sampling at X Hospital. The data is obtained using a questionnaire form. The results show, path analysis of occupational health and safety management system had a positive effect on the patient safety climate, teamwork had a positive effect on the patient safety climate, the work environment had a positive effect on patient safety climate, and the safety and health management system had a positive effect on the work environment, teamwork had a positive effect on the work environment. In the case of the mediating effect of the work environment, the correlation of the occupational health and safety management system and teamwork was also positive. Improved occupational health and safety management systems, as well as teamwork mediated by the work environment, will enhance the patient safety climate